1991
DOI: 10.2343/geochemj.25.377
|View full text |Cite
|
Sign up to set email alerts
|

Boron isotope fractionation accompanying boron mineral formation from aqueous boric acid-sodium hydroxide solutions at 25.DEG.C..

Abstract: A series of experiments was carried out in which boron minerals were precipitated from pH and chemical composition-controlled solutions at 25°C and boron isotope fractionation accompanying the mineral deposition was measured. Borax, sassolite and sborgite were synthesized from aqueous boric acid-sodium hydroxide solutions. Borax was obtained from solutions with higher pH and sassolite from solutions with lower pH, irrespective of the mole ratio of B and Na in the solution. The fractionation factor, S, defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
4
20
0
Order By: Relevance
“…5, all the data on S in the potassium borate system in Table 2 are plotted against the final pH of the solution phase given in Table 1. A trend is observed that the S value increases nearly linearly with increasing pH both for K2B4O7 and for suntite as in the case of borax in the previous paper (Oi et al, 1991). The slopes of the S-pH plots for the two potassium borates seem very similar to each other.…”
Section: Boron Isotope Fractionationsupporting
confidence: 61%
See 2 more Smart Citations
“…5, all the data on S in the potassium borate system in Table 2 are plotted against the final pH of the solution phase given in Table 1. A trend is observed that the S value increases nearly linearly with increasing pH both for K2B4O7 and for suntite as in the case of borax in the previous paper (Oi et al, 1991). The slopes of the S-pH plots for the two potassium borates seem very similar to each other.…”
Section: Boron Isotope Fractionationsupporting
confidence: 61%
“…At very high pH, KBO 2 ·1.33H 2 O and KBO 2 ·1.25H 2 O are found deposited. Sodium borate system Runs in this system were conducted to examine reproducibility of boron isotopic data in the previous paper (Oi et al, 1991 ). An XRD pattern of L2B2O4 obtained is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B preferentially condenses in B(OH) 3 and 10 B is incorporated in B(OH) 4 -, leading to isotopic fractionation (Kakihana et al, 1977;Oi et al, 1991;Palmer et al, 1987). The B isotope ratio (δ 11 B) in seawater averages +39.5‰ .…”
mentioning
confidence: 99%
“…The ratio between the two species was controlled using the 0 00 0 00 solution pH (Kakihana et al 1977). Recent studies have shown even greater fractionation between the two B species Oi et al 1991). These isotopic characteristics can be applied to study possible sources and the B process in pore water.…”
mentioning
confidence: 99%